2018
DOI: 10.1051/matecconf/201820103003
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a novel acoustic rain sensor with automated telemetry

Abstract: This paper presents the recent results of the design of a novel acoustic rainfall sensing system that is low-cost, portable, and easily deployable, which makes use of the recorded sound produced by the impact of the raindrops on the sensor surface. The sensor design allows the gathering of acoustic signal power and sending it to a server after a specified time interval, either through SMS or mobile internet connection. It exists in a weather-proof, standard-conformant, standalone system with its own power supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The nature and origin of the sound produced by drops striking a water surface were explored by Prokhorov & Chashechkin [132]. To date, acoustic recording of rainfall has been adopted in land-based research in only a small number of experimental studies (Trono et al [133], Guico et al [134], Avanzato & Beritelli [135], Dunkerley [136]), and has not yet found application in long-term rainfall monitoring.…”
Section: Acoustic Intensity Gaugesmentioning
confidence: 99%
“…The nature and origin of the sound produced by drops striking a water surface were explored by Prokhorov & Chashechkin [132]. To date, acoustic recording of rainfall has been adopted in land-based research in only a small number of experimental studies (Trono et al [133], Guico et al [134], Avanzato & Beritelli [135], Dunkerley [136]), and has not yet found application in long-term rainfall monitoring.…”
Section: Acoustic Intensity Gaugesmentioning
confidence: 99%
“…For rain detection (binary classification), a threshold of 0.1 mm/h was chosen to differentiate "rain pixels" from "No Rain pixels". Additionally, 6 classes were defined based on existing bibliography [19], see Table 1.…”
Section: B Categorical Focal Lossmentioning
confidence: 99%